Transformative Learning as Impact in Social Innovation. (2nd January 2019) - Yee, Joyce; Raijmakers, Bas; Ichikawa, Fumiko
Abstract: Measurable impact is an often expected and required outcome of innovation programs, and yet is particularly challenging for trying to understand social impact. The overt focus on economic value often overshadows other, more impactful social outcomes, such as learning, that emerge as a result of the work. In this paper, we use transformative learning theory (TLT) to explore the types and ranges of transformative learning that take place in design and social innovation (D&SI). TLT is an adult learning theory in which critical reflection is used to challenge the learner's beliefs and assumptions and can be particularly useful in helping us understand the perspective shifts important for participants of D&SI initiatives. Our aim is to reorient the discussion on D&SI impact by focusing on transformative learning as a form of social value. Using examples of and reflections on projects sited in various cultural contexts (Japan, UK, and Europe), this paper draws attention to the significance of transformative learning in contributing to social change and demonstrates the potential for addressing, framing, and communicating learning as one of the many important social impacts that occur in D&SI initiatives.